(untitled) (Cuadernos de Arqueología de la Universidad de Navarra, 2016)
The aim of this paper is to examine the relation between monumentality and connectivity of the cities on the Iberian Peninsula during the High Empire, using spatial and social network analyses. Firstly, the presence of the monuments under scrutiny (amphitheatre, circus and theatre) will be treated by a critical analysis of the different sources. Secondly, a social network analysis will be used to illuminate the role of Centrality in relation to the monumentality of cities. Naturally, the history of specific cities can explain their individual situation. However, large patterns cannot be understood by individual study of cities.